Disciples of flora : gardens in history and culture - Pagán, Victoria Emma, 1965-; Page, Judith W., 1951-; Weltman-Aron, Brigitte, 1961- (Cambridge Scholars Publishing, 2015)
'Disciples of Flora' explores, through a variety of approaches, disciplines, and historical periods, the place and vitality of gardens as cultural objects, repositories of meaning, and sites for the construction of identity and subjectivity; gardens being an eminent locus where culture and nature meet. This collection of essays contributes to a revision of histories of gardens by broadening the scope of scholarly inquiry to include a long history from ancient Rome to the present, in which contesting memories delineate new apprehensions of topography and space. The contributors draw attention t.